Implications of IFRS 16: leases - evidence from JSE-listed telecommunication companies - Raolane, Rirhandzu (College of Accounting, 2025)
This study investigates the implications of the new leasing standard, IFRS 16 Leases, on companies in the Telecommunications sector of the Johannesburg Stock Exchange. The International Accounting Standards Board's upcoming Post-Implementation Review of IFRS 16 is considered in this study (International Accounting Standards Board, 2023). IFRS 16, which is effective from 1 January 2019 (IFRS Foundation, 2016a), introduces requirements for lessees to present and disclose assets and liabilities that arise from leasing arrangements as part of their statement of financial position at initial recognition (IFRS Foundation, 2016a). The analysis of the impact is performed through a financial statement analysis, as well as financial ratio analysis, which is a different from the constructive capitalisation model developed by Imhoff et al. (1991, 1997). The findings of this study suggest that the implementation of IFRS 16 Leases led to a rise in reported assets and liabilities in the financial statements, which had an impact on key financial ratios for companies that rely on leased assets as part of their operations. The study's findings also show that as more leasing information is available, the implementation of IFRS 16 has led to financial statements that provide more transparent and comparable financial information.